Digital Classroom Services and Contribution to Strengthening Literacy Among Elementary School Students - Tias Pratiwi; Aprilia Tina Lidyasari; Wuri Wuryandani (LPPM Undiksha, 2026)
The advancement of digital technology has not automatically improved elementary students’ literacy, as its implementation is often unaccompanied by structured pedagogical design. Furthermore, the interplay among digital classroom services, instructional quality, and the supporting school ecosystem in strengthening literacy remains insufficiently examined. This study aims to analyze the implementation of digital classroom services in elementary education and their contribution to literacy enhancement. A qualitative case study design was employed in an elementary school implementing a digital classroom program. Participants included digital homeroom teachers, an ICT teacher, the curriculum coordinator, the principal, and digital-class students. Data were collected through semi-structured interviews, participant observations, and analysis of instructional documents and school policies. Data analysis followed the interactive model of data reduction, data display, and iterative conclusion drawing and verification, with source triangulation to ensure credibility. Findings reveal that digital classroom services operate as an integrated learning system combining synchronous and asynchronous activities via a learning management system. Literacy development was supported through structured reading strategies, metacognitive scaffolding, guiding questions, and systematic formative feedback. The study highlights the need for digital classroom development aligned with quality standards emphasizing TPACK-based instructional design, consistent formative assessment, strong school leadership, and sustainable school–family partnerships to effectively strengthen students’ literacy.